On r-dynamic Coloring of Ladder Graph and Tadpole Graph Using m-shadow Operation (Contemporary Mathematics, 2024)
An r-dynamic coloring is a proper k-coloring of a graph G = {V,E} such that the neighbors of every vertex v ∈ V(G) is colored using ς: V(G) → S(c) where S(c) is a set of colors. The coloring is made in such a way that it satisfies the conditions: (i) For any edge uv ∈ E(G), the color of u and color of v are distinct and (ii) The cardinality of coloring the neighbors of any vertex v should be greater than or equal to min{r, d(vG)}, where d(vG) is the degree of the vertex v. In this paper the lower bounds for the r-dynamic coloring of m-shadow graph of ladder graph Dm(Ln) and tadpole graph Dm(Ln,p) are attained. Using the lower bounds the exact solution of r-dynamic chromatic number of the ladder graph Ln and tadpole graph Ln,p by m-shadow operation are obtained.
Keywords: r-dynamic coloring; m-shadow graph; ladder graph; tadpole graph